Scale-Dependent Phenological Synchrony between Songbirds and Their Caterpillar Food Source - Hinks, A; Cole, E; Daniels, K; Wilkin, T; Nakagawa, S; Sheldon, B (University of Chicago Press, 2015)
In seasonal environments, the timing of reproduction has important fitness consequences. Our current understanding of the determinants of reproductive phenology in natural systems is limited because studies often ignore the spatial scale on which animals interact with their environment. When animals use a restricted amount of space and the phenology of resources is spatially variable, selection may favor sensitivity to small-scale environmental variation. Population-level studies of how songbirds track the changing phenology of their food source have been influential in explaining how populations adjust to changing climates but have largely ignored the spatial scale at which phenology varies. We explored whether individual great tits (Parus major) synchronize their breeding with phenological events in their local environment and investigated the spatial scale at which this occurs. We demonstrate marked variation in the timing of food availability, at a spatial scale relevant to individual birds, and that such local variation predicts the breeding phenology of individuals. Using a 45-year data set, we show that measures of vegetation phenology at very local scales are the most important predictors of timing of breeding within years, suggesting that birds can fine-tune their phenology to that of other trophic levels. Knowledge of the determinants of variation in reproductive behavior at different spatial scales is likely to be critical in understanding how selection operates on breeding phenology in natural populations.